EFISIENSI BELANJA PEMERINTAH DAERAH DALAM MENURUNKAN TINGKAT KEMISKINAN SAAT PANDEMI COVID-19 DI PROVINSI ACEH - Sakinah Setyo; Roosemarina Anggraini Rambe (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This study aims to measure the efficiency of local government expenditures in poverty reduction in 23 regencies and cities in Aceh Province during the COVID-19 pandemic. The study is quantitative descriptive research. The research method applied is Data Envelopment Analysis (DEA) based on input-oriented model with the Variable Return to Scale approach. Output is poverty rate. Three inputs used are education, health, and social protection expenditures per capita. The results show that out of the 23 regencies and cities in Aceh Province, only five regencies and cities are relatively efficient, there are Aceh Utara, Bireun, Banda Aceh, Lhokseumawe, and Aceh Tamiang. Four peers in Aceh Province are Aceh Utara, Bireun, Banda Aceh, Lhokseumawe. The most efficient is Bireun regency. To be efficient, the inefficient regencies and cities’ governments should reduce their expenditures, especially education expenditure, which is the biggest source of inefficiency